Intrinsic Deregulation of Vascular Smooth Muscle and Myofibroblast Differentiation in Mesenchymal Stromal Cells from Patients with Systemic Sclerosis. - Björn Hegner; Theres Schaub; Rusan Catar; Angelika Kusch; Philine Wagner; Kirill Essin; Claudia Lange; Gabriela Riemekasten; Duska Dragun (PLoS ONE, 2016)
INTRODUCTION:Obliterative vasculopathy and fibrosis are hallmarks of systemic sclerosis (SSc), a severe systemic autoimmune disease. Bone marrow-derived mesenchymal stromal cells (MSCs) from SSc patients may harbor disease-specific abnormalities. We hypothesized disturbed vascular smooth muscle cell (VSMC) differentiation with increased propensity towards myofibroblast differentiation in response to SSc-microenvironment defining growth factors and determined responsible mechanisms. METHODS:We studied responses of multipotent MSCs from SSc-patients (SSc-MSCs) and healthy controls (H-MSCs) to long-term exposure to CTGF, b-FGF, PDGF-BB or TGF-β1. Differentiation towards VSMC and myofibroblast lineages was analyzed on phenotypic, biochemical, and functional levels. Intracellular signaling studies included analysis of TGF-β receptor regulation, SMAD, AKT, ERK1/2 and autocrine loops. RESULTS:VSMC differentiation towards both, contractile and synthetic VSMC phenotypes in response to CTGF and b-FGF was disturbed in SSc-MSCs. H-MSCs and SSc-MSCs responded equally to PDGF-BB with prototypic fibroblastic differentiation. TGF-β1 initiated myofibroblast differentiation in both cell types, yet with striking phenotypic and functional differences: In relation to H-MSC-derived myofibroblasts induced by TGF-β1, those obtained from SSc-MSCs expressed more contractile proteins, migrated towards TGF-β1, had low proliferative capacity, and secreted higher amounts of collagen paralleled by reduced MMP expression. Higher levels of TGF-β receptor 1 and enhanced canonical and noncanonical TGF-β signaling in SSc-MSCs accompanied aberrant differentiation response of SSc-MSCs in comparison to H-MSCs. CONCLUSIONS:Deregulated VSMC differentiation with a shift towards myofibroblast differentiation expands the concept of disturbed endogenous regenerative capacity of MSCs from SSc patients. Disease related intrinsic hyperresponsiveness to TGF-β1 with increased collagen production may represent one responsible mechanism. Better understanding of repair barriers and harnessing beneficial differentiation processes in MSCs could widen options of autologous MSC application in SSc patients.